2010
DOI: 10.1002/jor.21115
|View full text |Cite
|
Sign up to set email alerts
|

Cefazolin embedded biodegradable polypeptide nanofilms promising for infection prevention: A preliminary study on cell responses

Abstract: Implant-associated infection is a serious complication in orthopedic surgery, and endowing implant surfaces with antibacterial properties could be one of the most promising approaches for preventing such infection. In this study, we developed cefazolin loaded biodegradable polypeptide multilayer nanofilms on orthopedic implants. We found that the amount of cefazolin released could be tuned. A high local concentration of cefazolin was achieved within the first a few hours and therefore may inhibit bacterial col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
30
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 34 publications
2
30
0
Order By: Relevance
“…Despite the difference in treatment duration between the current and previous studies, our data are consistent with several other studies in which shorter time periods were used and/or difference cell types were studied. 12,14,15,[17][18][19][20][21][22][23] This similarity both adds validity to our data and suggests that the negative effects imparted by high levels of antibiotics in this study may be a result of changes that occur at early time points.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Despite the difference in treatment duration between the current and previous studies, our data are consistent with several other studies in which shorter time periods were used and/or difference cell types were studied. 12,14,15,[17][18][19][20][21][22][23] This similarity both adds validity to our data and suggests that the negative effects imparted by high levels of antibiotics in this study may be a result of changes that occur at early time points.…”
Section: Discussionsupporting
confidence: 77%
“…For example, the cephalosporin cefurotoxime has the potential to increase ALP activity and proliferation, 23 and a cefazolin-loaded biodegradable polypeptide multilayer nanofilm improved osteoblast viability and proliferation. 12 Although we did not use the same doses as others for the cephalosporins, and although not significant, we observed a trend for increases in ALP activity for the cephalosporins as well (Fig. 2D-F).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…[21] Different surface modifications and coating techniques can be used, such as direct impregnation with antibiotics and immobilization of an antimicrobial agent in a matrix capable of binding to different surfaces, [22] as well as coating with antimicrobial, active metals such as copper and silver, [23] nitric oxide-releasing materials [24] and titanium dioxide films. [25] Ainslie et al [26] have shown in vitro that nanostructured surfaces display reduced inflammation in comparison with a respective flat control.…”
Section: Implant-associated Infection and Nanotechnologymentioning
confidence: 99%
“…Li et al [21] developed biodegradable polypeptide multilayer nanofilms to potentially serve as antibiotic carriers at the implant-tissue interface. They demonstrated that polypeptide multilayer nanofilms, with or without cefazolin, have antibacterial activity against organisms frequently associated with osteomyelitis, and may improve bone healing through improving osteoblast cell adhesion, viability, and proliferation.…”
Section: Implant-associated Infection and Nanotechnologymentioning
confidence: 99%